2021
DOI: 10.1177/00033197211039921
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for the early prediction of contrast-induced nephropathy after percutaneous coronary intervention in adults: A systematic review and meta-analysis

Abstract: Contrast-induced nephropathy (CIN) is a complication of patients undergoing percutaneous coronary intervention (PCI). Promising biomarkers for the early prediction of CIN can significantly improve outcomes of these patients. We searched PubMed, EMBASE, Web of Science, and Cochrane Library for studies. Trials reporting an area under the curve (AUC) for the utility of novel biomarkers in the early prediction of CIN in adults after PCI were included. In total, 42 studies comprising 11,984 adult patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The meta-analysis by Yi He ( 62 ) et al and Lareyere et al ( 63 ) showed non-inferior results compared to cystatin C performance. Compared with IL-18, KIM-1, L-FABP, CRP, and BNP, NGAL exhibited increased predictive value in CI-AKI after PCI ( 64 ). However, Sharrod-Cole et al reported the utility of plasma NGAL in patients undergoing CABG as inconclusive of CI-AKI prediction ( 65 ).…”
Section: Risk Stratification and Predictionmentioning
confidence: 99%
“…The meta-analysis by Yi He ( 62 ) et al and Lareyere et al ( 63 ) showed non-inferior results compared to cystatin C performance. Compared with IL-18, KIM-1, L-FABP, CRP, and BNP, NGAL exhibited increased predictive value in CI-AKI after PCI ( 64 ). However, Sharrod-Cole et al reported the utility of plasma NGAL in patients undergoing CABG as inconclusive of CI-AKI prediction ( 65 ).…”
Section: Risk Stratification and Predictionmentioning
confidence: 99%
“…There is evidence that AKI is a phenomenon associated with the activation of proinflammatory cytokines, and with this, it calls for the use of markers of kidney injury (27). Some biomarkers predict AKI(37); however, the high costs and lack of availability of these tests in our region forced us to use biochemical parameters that are within reach in our practice to predict AKI events. PCT is barely detectable in healthy individuals; however, diverse conditions tend to elevate it (surgery, trauma, burns, pancreatitis, and sepsis), where levels can be markedly high (38-42).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that AKI is a phenomenon associated with the activation of proinflammatory cytokines and therefore calls for the use of markers of kidney injury [ 27 ]. Some biomarkers predict AKI [ 42 ]. However, the high cost and lack of availability of these tests in our region forced us to use biochemical parameters more within reach in our practice in order to predict AKI events.…”
Section: Discussionmentioning
confidence: 99%